KEMAMPUAN MENULIS CERPEN SISWA KELAS X SMA NEGERI 9 SIJUNJUNG DENGAN TEKNIK MENYELESAIKAN CERITA - Gusnita, Zilvicha; Nisja, Indriani; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2013)
The research on the background by students difficulties in proposing their ideas while writing short story. Furthermore, the technique of learning which is used by the teachers are not vary. The teachers also are not able to motivate students in helping them to bring up their ideas. According to those problems,Â  the researcher do the research writing short story by finishing the story technique. The purpose of this research is to describe the capability of SMA Negeri 9 Sijunjung class X students in writing short story. The research is used Semi theory about writing, Thahar theory Â about short story, and Tarigan theory about the technique of finishing story.This research is a quantitative research with descriptive method. The population in this research is about 130 students which are dispersed in five classes. Those students are listed in 2012/2013 period. The sample of the research is about 26 students by purposive sampling technique. The researcher choose X.I class as the sample of the research. It is considered by variety of students ability. Later on, the research data is to test ferformance to research the ability writing short story with the technique.According to the result of data analysis, it shows that the ability in writing short story of SMA Negeri 9 Sijunjung students by finishing story technique as (1) students ability in describing the characters in writing short story are classified enough with the avarage of mastery 73.23%, (2) studentsâ ability in using plot of the story are classified enough with the avarage of mastery 56-65%, (3) studentsâ ability in using background of the story are classified more than enough with the avarage of mastery 71.92%. As a result, it can be conluded that studentsâ abitlity in writing short story with finishing story techniqueare classified more than enough with the avarage 67.76% in the stretch of 66.75%.